PRONOMINA DALAM BAHASA DAYAK BIDAYUH LAWANG DI KABUPATEN BENGKAYANG - Jupri Jupri; Amriani Amir; Agus Syahrani (Universitas Tanjungpura, 2020)
AbstractThis research deals with the field of morphology, especially regarding pronouns in BDBL in Bengkayang Regency. This research was motivated by the ins and outs of word structure and the influence of changes in word structure on word classes and meaning of words in the Dayak Bidayuh Lawang language. This research used descriptive linguistic method with a qualitative form. The data source in this research was Dayak Bidayuh Lawang language in Bengkayang Regency in the types of pronouns in Dayak Bidayuh language. The data collection technique used was the recording and note taking technique with data collection tools in the form of a list of types of pronouns in Indonesian, and then translated into the Dayak Bidayuh Lawang language. Based on the analysis results, it can be concluded that in BDBL there were six types of pronouns namely, personal pronouns, possessive, demonstrative, interrogative, relative, and in determinative. The forms of pronouns in BDBL consist of free forms and bound forms, and the functions of pronouns in BDBL in Bengkayang Regency generally occupy functions as subjects, objects, and predicates.Keywords: Pronouns in Dayak Bidayuh Lawang Language (BDBL) inBengkayang Regency